1998
DOI: 10.1093/jnci/90.16.1225
|View full text |Cite|
|
Sign up to set email alerts
|

Modification of Clinical Presentation of Prostate Tumors by a Novel Genetic Variant in CYP3A4

Abstract: We determined that a single base change in the 5' flanking region of the CYP3A4 gene was associated with higher clinical stage and grade in men with prostate tumors. Our results suggest that mutations in the CYP3A4 gene may influence prostate carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
226
1
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(241 citation statements)
references
References 13 publications
9
226
1
5
Order By: Relevance
“…15 A number of sequence variants at the CYP3A locus have been identified, but few of them have been definitively associated with alterations in mRNA or protein levels and/or CYP3A function. The CYP3A4*1B allele, originally reported to be associated with advanced clinical grade of prostate tumors, 16 is a common SNP located in the 5 0 flanking region. A number of nonsynonymous (ns) SNPs have been reported for CYP3A4, but most occur at low frequency.…”
Section: Introductionmentioning
confidence: 99%
“…15 A number of sequence variants at the CYP3A locus have been identified, but few of them have been definitively associated with alterations in mRNA or protein levels and/or CYP3A function. The CYP3A4*1B allele, originally reported to be associated with advanced clinical grade of prostate tumors, 16 is a common SNP located in the 5 0 flanking region. A number of nonsynonymous (ns) SNPs have been reported for CYP3A4, but most occur at low frequency.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 This variant has the highest frequency in African-Americans, mid-frequency in Caucasians, and lowest frequency in Asians, 35,36 re¯ecting relative prostate cancer rates in these populations. The CYP3A4 variant was associated with prostate cancer risk in Caucasians 23 and African-Americans 36 in case ± control studies.…”
Section: Genes Involved In Androgen Metabolism and Regulation In The mentioning
confidence: 96%
“…In addition, genetic studies have revealed an association between genetic variants of the natural resistance-associated macrophage protein (NRAMP1) and VDR genes and smearpositive pulmonary TB (15). Evidence regarding the 1,25(OH) 2 D3-VDR complex has shown that after binding to the RXR heterodimer, this complex interacts with the PXR response elements on the CYP3A4 gene promoter (12,16). It suggests that CYP3A4 enzymes or signaling involving CYP3A4 may be associated with susceptibility to the development of pulmonary TB.…”
Section: D3] Similarmentioning
confidence: 99%